Consumer Electronics and Historical Analysis of The Impact of Effective Adoption of Cloud Computing in Higher Education (Vallis Aurea, 2023)
Cloud computing in the Educational sector has immensely enhanced academic performance in the developed nations and the professional contributions may benefit the education strategy of Nigeria particularly in transforming the traditional education model to computer based virtual applications with a focus on e-pedagogy. Cloud computing remains a paradox and open to academic debate with respect to business adoption of its utility, and studies depict that cloud computing to an extent is still at its early incubation in institutions of higher learning; that also affirms the infancy of cloud computing in academia, and this has caused the dearth of a unified definition and understanding of cloud computing. However, this study will develop academic definition and meaning of cloud computing with reference to institutional applications This study will also explore the benefits of cloud computing in learning, and focus on the development of relevant models for resource usage in higher education institutions. Author shows that successful adoption of cloud computing by various educational institutions in Nigeria depends on their transition strategies in terms of resource acquisition and deployment. These strategies could form barriers in delivering effective teaching learning, and assessment of instruments encountered through migrating to the cloud. Hence this study is geared towards bridging the gap between the usage of cloud computing in education and effective delivery of educational services via the 'cloud' in Higher Education Institutions (HEIs) in Nigeria.